Synthesis and Characterization of Fe-Doped CaTiO3 Polyhedra Prepared by Molten NaCl Salt - Dwi Rahayu Novianti; Fikri Haikal; Usman Ali Rouf; Arie Hardian; Anton Prasetyo (Science and Technology Indonesia, 2022)
CaTiO3 as one of the perovskite-based photocatalysts has a band gap energy of 3.5 eV (~354 nm), thus will work at the ultraviolet light region. One of the strategies to decrease the band gap energy is doping metal. In this research, CaTiO3 was doped by Fe element as purposes to decreasing its band gap energy. Fe doped CaTiO3 compounds were synthesized using molten NaCl salt method. The diffractogram samples showed that the Fe-doped CaTiO3 crystal was successfully prepared. Meanwhile, the SEM images showed that the particle shape was regular polyhedral morphology, and doping Fe3+ caused the particle size to decrease and agglomerated. The UV-Vis DRS spectra showed that the Fe-dopant revealed the absorption light at visible range wavelength.